CORPORATE GOVERNANCE AS AN AREA OF REGULATORY ARBITRAGE - Adamska, Agata (Ekonomia i Prawo. Economics and Law, 2013)
There are many corporate governance systems that exist in the world. Although two of them, an open (outsider system) and a closed (insider system) one are enumerated as the two leading systems, detailed regulations form a significant diversification of solutions that result from their national character. These differences in corporate governance systems constitute one of the factors that determine global flow of capital, since companies as well as investors do take large-scale advantage of regulatory arbitrage in their quest for optimum solutions from their perspective. The regulators that create institutional framework of capital markets, at the same time do influence the competitive advantage of the given country as the investment destination, and thus affect its economy development potential . Such situation creates the temptation to relax requirements for companies and investors. On the one hand it reduces the market entry barriers and allows to attract more investment capital. On the other hand, it stands for the upsurge of speculative capital and of the capital of unknown provenance, which may destabilize economy. The system of corporate governance solutions should then be balanced and take account of the need to remain competitive in the market as well as strengthening and protection of its reputation.